Internet television an initial market assessment - Tusara, Laarni M.; Cruz, Edison D. (Quezon City University of the Philippines Diliman, 2007)
Traditional and new television content are more commonly seen over the Internet due to the advances in technology. Increase in speed of Internet connection and total Internet users and decrease in connection cost allows the convergence of Internet and television, two media which were once seen separately to deliver distinct purposes. The move from broadcast television to broadband television only entails wider content selection for Internet users. Local free television as well as cable and satellite companies can only offer as much channels, but come the blurring of Internet and television, it is but unimaginable to see the vastness of possible content features available. This study looks at the potential of a new technology where television content is delivered through broadband network instead of the usual broadcast and cable formats. Internet Television is already present in more technologically advanced areas in Europe and the United States. It has been criticized for a number of hurdles like the lack of set top boxes to convert analog channels to digital format, low bandwidth in the household, and the anticipated poor quality of the streaming video. Internet TV however offers interactivity and convergence. The broadcast industry recognized that more television shows are also viewed through new media devices apart from the tradition television sets. Mobile phones, iPod and especially the Internet, are venues where one can provide content for television viewers and Internet users alike. The immergence of these new media would offer opportunities for broadcast companies apart from the revenues generated from airtime sales. Since we are dealing with a new technology, it is important to identify key product and market information valued by the potential subscribers of Internet Television. This study intends to determine the features that are considered strengths and weaknesses of Internet Television, substantiate how much the market is willing to pay for the subscription of Internet Television and identify the market segment most likely to use Internet Television. The Theory of Reasoned Action developed by Ajzan and Fishbien in 1967 was used as the framework for this research. Theory of Reasoned Action implies that prior attitude toward the behavior and the present subjective norms influence an individual's intention. A person will normally act in accordance with his intentions. Thus, the easiest way to predict a behavior, for example, whether a consumer will purchase a product, like Internet TV is to simply ask if they are interested to subscribe to Internet TV. The attitude and subjective norms are operationalized through factors like market needs, wants, considerations, influences, etc. This research used a concept test questionnaire administered through face to face and email to 115 respondents purposively chosen. Concept testing is a special method in market research that assesses new product idea. This is very useful since the market's preference and purchase intentions are exploded before the actual launch of the product. For the purpose of this study, the Internet Television concept, made by the researcher reads : Internet TV give you choice and convenience. You can count on having a wide choice of archived features like movies, television shows and series, music videos, concerts, interviews, documentaries, etc., ready to be retrieved anytime, whenever you want. With INTERNET TV, you will experience the convenience of watching whatever you want, in the comfort of your own home. No need to wait for regular programming. No need to rent or purchase CDs. On top of this is a variety of channels (i.e., local. International, cartoon, video, entertainment, news, sports), available in quality reception. The choices are just unlimited with INTERNET TV. Hold your remote control and everything is just a click away. This study is limited to the concept introduced. The respondent's understanding of the concept is reflected on the data which may affect the accuracy of the analysis. Data analysis is based on the research framework. This quantitative descriptive study explores the following market factors : purchase intentions (behavior); needs, likes, dislikes, important considerations, willingness to pay, superiority over substitute product, influences (attitude); perceived users and demographics (subjective norms). Attitude and subjective norms indicators were compared with behavior indicator. Research findings and discussion were presented in three parts, specifically to address the three research objectives. Product evaluation determines features that the market considers as Internet TV strengths and weaknesses. Value Analysis substantiates how much the market is willing to pay for Internet TV, among set packages and bundle. Segment analysis identifies the market segment most likely to use Internet Television.

Interesting findings emerged from this research design. There is generally a high level of purchase intention for Internet TV among the respondents. The product's major strengths are convenience and choice and its major weaknesses is the perceived high cost. Most of them are willing to pay less than P1000 for this subscription. Considering the viable cost of this new technology, the market segment most likely to subscribe for Internet TV are those from the older segment, belonging to the ABC socio-economic bracket. There is only a moderate need for Internet TV, in contrast with a high level of interest for purchase. Substitute products such as cable television and DVDs are factors that influence the felt moderate need for the product. It seems that respondents' current needs like watching news, soap opera, or cable movies are already generally addressed by cable channels and DVDs. Internet TV's stronger competition among the two substitute products is the DVD since among those who have DVD players at home, majority consider DVD as a better product than Internet TV while only a few of those with cable TV connection consider cable TV as a better option than having Internet TV. This may be connected to the finding that respondents value the convenience of watching television content when you want it and the wide variety of television content readily available. In essence, convenience and choice are partly already addressed by DVD, in contrast with cable TV where viewers are still required to wait for regular programming. Price is a critical factor in the purchase intention of the respondents. It is also an equally critical factor in this analysis since the major weakness recognized for Internet Television is the anticipated high cost of subscription. The P1000 willingness to pay for Internet TV is a little over if not equal to the current cable television rates. Technology-wise, a P1000 worth of Internet Television is far reached--foreign companies, Comcast for example, offers 33 dollars per month rate. Most of the respondents are only willing to pay P500 and below. There is also a broad discrepancy in willingness to pay i.e., as low as P100, which is very unrealistic to as high as P5000. With this hope, Internet Television may readjust its features to get higher willingness to pay from the market. The data also looked at willingness to pay for packages and bundle. Average willingness to pay doubles with the addition of Internet broadband connection or with VoIP. Comcast, offers 99 dollars per month for triple play or Internet TV + broadband connection + VoIP. The trade-off between the high cost of Internet TV and the willingness to pay of interested respondents reveal that triple play is the most viable package since among those with high purchase intention, most are willing to pay more than P1000 for Internet TV. The market segments most likely to subscribe to Internet TV are those from the ABC socio-economic bracket and those from the older group i.e., parents since they have higher purchasing power. The parents consider the needs and wants of the young group i.e., teens, students and kids. Internet TV, being home-based takes on the advantage of the nature of television watching as a family experience. More research is however needed to probe deeply into the needs and wants of the ABC market, being the group more likely to purchase Internet TV. While this study sees that the parents (older group) should be the target of product campaigns, kids' insights are also needed to explore on their possible influence in their parents' purchases. Corollary with these, proposals for relevant areas for study were offered. Since only an initial assessment, the nature and form of data gathering procedure, being a purely quantitative in design decreases the validity of the data inferred in the study. Thus, methodological implications as well as instruments, designs and focus for future related researchers were raised.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Internet television; Technology assessment